简体   繁体   English

这段混淆的 Haskell 代码是如何工作的?

[英]How does this piece of obfuscated Haskell code work?

While reading https://en.uncyclopedia.co/wiki/Haskell (and ignoring all the "offensive" stuff), I stumbled upon the following piece of obfuscated code:在阅读https://en.uncyclopedia.co/wiki/Haskell (并忽略所有“令人反感”的东西)时,我偶然发现了以下一段混淆代码:

fix$(<$>)<$>(:)<*>((<$>((:[{- thor's mother -}])<$>))(=<<)<$>(*)<$>(*2))$1

When I run that piece of code in ghci (after importing Data.Function and Control.Applicative ), ghci prints the list of all powers of 2.当我在ghci运行那段代码时(在导入Data.FunctionControl.Applicative ), ghci打印出 2 的所有幂的列表。

How does this piece of code work?这段代码是如何工作的?

To begin with, we have the lovely definition首先,我们有一个可爱的定义

x = 1 : map (2*) x

which by itself is a bit mind-bending if you've never seen it before.如果您以前从未见过它,这本身就有点令人费解。 Anyway it's a fairly standard trick of laziness and recursion.无论如何,这是一个相当标准的懒惰和递归技巧。 Now, we'll get rid of the explicit recursion using fix , and point-free-ify.现在,我们将使用fix和 point-free-ify 摆脱显式递归。

x = fix (\vs -> 1 : map (2*) vs)
x = fix ((1:) . map (2*))

The next thing we're going to do is expand the : section and make the map needlessly complex.我们要做的下一件事是扩展:部分并使map变得不必要地复杂。

x = fix ((:) 1 . (map . (*) . (*2)) 1)

Well, now we have two copies of that constant 1 .好吧,现在我们有这个常量1两个副本。 That will never do, so we'll use the reader applicative to de-duplicate that.那永远不会,所以我们将使用 reader applicative 去重复它。 Also, function composition is a bit rubbish, so let's replace that with (<$>) wherever we can.此外,函数组合有点垃圾,所以让我们尽可能用(<$>)替换它。

x = fix (liftA2 (.) (:) (map . (*) . (*2)) 1)
x = fix (((.) <$> (:) <*> (map . (*) . (*2))) 1)
x = fix (((<$>) <$> (:) <*> (map <$> (*) <$> (*2))) 1)

Next up: that call to map is much too readable.接下来:对map调用太易读了。 But there's nothing to fear: we can use the monad laws to expand it a bit.但是没有什么可害怕的:我们可以使用单子定律来扩展它。 In particular, fmap fx = x >>= return . f特别是, fmap fx = x >>= return . f fmap fx = x >>= return . f , so fmap fx = x >>= return . f , 所以

map f x = x >>= return . f
map f x = ((:[]) <$> f) =<< x

We can point-free-ify, replace (.) with (<$>) , and then add some spurious sections:我们可以点自由化,将(.)替换为(<$>) ,然后添加一些虚假部分:

map = (=<<) . ((:[]) <$>)
map = (=<<) <$> ((:[]) <$>)
map = (<$> ((:[]) <$>)) (=<<)

Substituting this equation in our previous step:代入我们上一步中的这个等式:

x = fix (((<$>) <$> (:) <*> ((<$> ((:[]) <$>)) (=<<) <$> (*) <$> (*2))) 1)

Finally, you break your spacebar and produce the wonderful final equation最后,你打破你的空格键并产生美妙的最终方程

x=fix(((<$>)<$>(:)<*>((<$>((:[])<$>))(=<<)<$>(*)<$>(*2)))1)

Was writing a long answer with a full run-through of my IRC logs of the experiments leading up to the final code (this was in early 2008), but I accidentally all the text :) Not that much of a loss though - for the most part Daniel's analysis is spot on.正在写一个很长的答案,其中包含导致最终代码的实验的完整运行 IRC 日志(这是在 2008 年初),但我不小心写下了所有文本:) 虽然损失不大 - 对于Daniel 的大部分分析都恰到好处。

Here's what I started with:这是我的开始:

Jan 25 23:47:23 <olsner>        @pl let q = 2 : map (2*) q in q
Jan 25 23:47:23 <lambdabot>     fix ((2 :) . map (2 *))

The differences mostly come down to the order in which the refactorings happened.差异主要归结为重构发生的顺序。

  • Instead of x = 1 : map (2*) x I started with 2 : map ... , and I kept that initial 2 right up until the very last version, where I squeezed in a (*2) and changed the $2 at the end into $1 .而不是x = 1 : map (2*) x我开始用2 : map ... ,我不停,最初的2右,直到最后的版本,在这里我在挤(*2)并改变了$2处最后变成$1 The "make the map needlessly complex" step didn't happen (that early). “使地图不必要地复杂”这一步没有发生(那么早)。
  • I used liftM2 instead of liftA2我用liftM2代替liftA2
  • The obfuscated map function was put in before replacing liftM2 with Applicative combinators.在用 Applicative 组合器替换 LiftM2 之前,引入了混淆的map函数。 That's also when all the spaces disappeared.这也是所有空间消失的时候。
  • Even my "final" version had lots of .甚至我的“最终”版本也有很多. for function composition left over.用于剩余的函数组合。 Replacing all of those with <$> apparently happened some time in the months between that and uncyclopedia.<$>替换所有这些显然发生在那个和 uncyclopedia 之间的几个月里。

BTW, here's an updated version that no longer mentions the number 2 :顺便说一句,这是一个不再提及数字2的更新版本:

fix$(<$>)<$>(:)<*>((<$>((:[{- Jörð -}])<$>))(=<<)<$>(*)<$>(>>=)(+)($))$1

Both answers derive the obfuscated code snippet from the short original given out of the blue, but the question actually asks how does the long obfuscated code do its job.这两个答案都是从突然给出的简短原始代码中得出混淆代码片段的,但问题实际上是问长混淆代码如何完成其​​工作。

Here's how:就是这样:

fix$(<$>)<$>(:)<*>((<$>((:[{- thor's mother -}])<$>))(=<<)<$>(*)<$>(*2))$1 
= {- add spaces, remove comment -}
fix $ (<$>) <$> (:) <*> ( (<$> ((:[]) <$>) ) (=<<)  <$>  (*)  <$>  (*2) ) $ 1 
--                      \__\______________/_____________________________/
= {-    A   <$> B   <*> C                          $ x   =   A (B x) (C x) -}
fix $ (<$>) (1 :)     ( ( (<$> ((:[]) <$>) ) (=<<)  <$>  (*)  <$>  (*2) ) 1 )
--                      \__\______________/____________________________/
= {- op f g = (f `op` g) ; (`op` g) f = (f `op` g) -}
fix $ (1 :) <$>  ( (((=<<) <$> ((:[]) <$>) )        <$>  (*)  <$>  (*2) ) 1 )
--                  \\____________________/____________________________/
= {- <$> is left associative anyway -}
fix $ (1 :) <$>  ( ( (=<<) <$> ((:[]) <$>)          <$>  (*)  <$>  (*2) ) 1 )
--                  \__________________________________________________/
= {- A <$> foo = A . foo when foo is a function -}
fix $ (1 :) <$>  ( ( (=<<) <$> ((:[]) <$>)           .   (*)   .   (*2) ) 1 )
--                  \__________________________________________________/
= {- ((:[]) <$>) = (<$>) (:[]) = fmap (:[])  is a function -}
fix $ (1 :) <$>  ( ( (=<<)  .  ((:[]) <$>)           .   (*)   .   (*2) ) 1 )
--                  \__________________________________________________/
= {- (a . b . c . d) x = a (b (c (d x))) -}
fix $ (1 :) <$>      (=<<)  (  ((:[]) <$>)           (   (*)   (   (*2)   1 )))
= {- (`op` y) x = (x `op` y) -}
fix $ (1 :) <$>      (=<<)  (  ((:[]) <$>)           (   (*)   2             ))
= {- op x = (x `op`) -}
fix $ (1 :) <$>      (=<<)  (  ((:[]) <$>)              (2*)                  )
= {-  (f `op`) g = (f `op` g) -}
fix $ (1 :) <$>      (=<<)  (   (:[]) <$>               (2*)                  )
= {-  A <$> foo = A . foo when foo is a function -}
fix $ (1 :) <$>      (=<<)  (   (:[])  .                (2*)                  )
= {-  (f . g) = (\ x -> f (g x)) -}
fix $ (1 :) <$>      (=<<)  (\ x -> [2*x]  )
= {- op f = (f `op`)  -}
fix $ (1 :) <$>           ( (\ x -> [2*x]  )  =<<)

Here ( (\\ x -> [2*x]) =<<) = (>>= (\\ x -> [2*x])) = concatMap (\\ x -> [2*x]) = map (2*) is a function, so again, <$> = .这里( (\\ x -> [2*x]) =<<) = (>>= (\\ x -> [2*x])) = concatMap (\\ x -> [2*x]) = map (2*)是一个函数,所以<$> = . :

= 
fix $ (1 :)  .  map (2*)
= {- substitute the definition of fix -}
let xs = (1 :) . map (2*) $ xs in xs
=
let xs = 1 : [ 2*x | x <- xs] in xs
= {- xs = 1 : ys -}
let ys =     [ 2*x | x <- 1:ys] in 1:ys
= {- ys = 2 : zs -}
let zs =     [ 2*x | x <- 2:zs] in 1:2:zs
= {- zs = 4 : ws -}
let ws =     [ 2*x | x <- 4:ws] in 1:2:4:ws
=
iterate (2*) 1
= 
[2^n | n <- [0..]]

are all the powers of 2 , in increasing order.都是2的幂,按升序排列。


This uses这使用

  • A <$> B <*> C $ x = liftA2 ABC x and since liftA2 ABC is applied to x it's a function, an as a function it means liftA2 ABC x = A (B x) (C x) . A <$> B <*> C $ x = liftA2 ABC x并且因为liftA2 ABC被应用到x它是一个函数,作为一个函数它意味着liftA2 ABC x = A (B x) (C x)
  • (f `op` g) = op fg = (f `op`) g = (`op` g) f are the three laws of operator sections (f `op` g) = op fg = (f `op`) g = (`op` g) f是算子部分的三个定律
  • >>= is monadic bind, and since (`op` g) f = op fg and the types are >>=(`op` g) f = op fg绑定,因为(`op` g) f = op fg并且类型是

    (>>=) :: Monad m => ma -> (a -> mb ) -> mb (\\ x -> [2*x]) :: Num t => t -> [ t] (>>= (\\ x -> [2*x])) :: Num t => [ t] -> [ t]

    by type application and substitution we see that the monad in question is [] for which (>>= g) = concatMap g .通过类型应用和替换,我们看到所讨论的 monad 是[]其中(>>= g) = concatMap g

  • concatMap (\\ x -> [2*x]) xs is simplified as concatMap (\\ x -> [2*x]) xs简化为

    concat $ map (\\ x -> [2*x]) = concat $ [ [2*x] | x <- xs] = [ 2*x | x <- xs] = map (\\ x -> 2*x )
  • and by definition,根据定义,

     (f . g) x = f (gx) fix f = let x = fx in x iterate fx = x : iterate f (fx) = x : let y = fx in y : iterate f (fy) = x : let y = fx in y : let z = fy in z : iterate f (fz) = ... = [ (f^n) x | n <- [0..]]

    where在哪里

     f^n = f . f . ... . f -- \\_____n_times _______/

    so that以便

    ((2*)^n) 1 = ((2*) . (2*) . ... . (2*)) 1 = 2* ( 2* ( ... ( 2* 1 )...)) = 2^n , for n in [0..]

声明:本站的技术帖子网页,遵循CC BY-SA 4.0协议,如果您需要转载,请注明本站网址或者原文地址。任何问题请咨询:yoyou2525@163.com.

 
粤ICP备18138465号  © 2020-2024 STACKOOM.COM